Transformation of Islamic Education in Responding to National and Global Issues: A Case Study of Strengthening National Values and Social Justice at Sekolah Dasar Islam Terpadu Daar El Falah Cianjur - Uus Ruswandi; Rusman Nurdiansyah; Raka Akhmad Hilman Nurwahyu; Sofwan Gozali; Mohamad Erihadiana (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
Islamic education at the elementary school level faces various challenges arising from national and global issues, including globalization, digital transformation, declining national awareness, and social inequality. These challenges require educational institutions to transform their approaches in order to remain relevant and responsive to contemporary societal needs. This study aims to analyze the transformation of Islamic education in strengthening national values and social justice at Daar El Falah Integrated Islamic Elementary School (SDIT Daar El Falah) Cianjur. The research employs a qualitative case study approach through observations, interviews, and document analysis. The findings indicate that the transformation of Islamic education is reflected in the integration of Islamic and national values within the curriculum, contextual learning practices, the development of an inclusive school culture, and the strengthening of teachers’ roles as agents of character formation. These efforts contribute to fostering nationalism, tolerance, social responsibility, and awareness of justice among students. The study concludes that Islamic education at SDIT Daar El Falah plays a strategic role in preparing students to respond constructively to national and global challenges while upholding Islamic values, national identity, and social justice.